A Novel System to Diagnose Cutaneous Adverse Drug Reactions Employing the Cellscan—Comparison with Histamine Releasing Test and Inf-γ Releasing Test - Ilan Goldberg; Boris Gilburd; Martine Szyper Kravitz; Shmuel Kivity; Berta Ben Chaim; Tirza Klein; Yael Schiffenbauer; Ela Trubniykovr; Sarah Brenner; Yehuda Shoenfeld (Clinical and Developmental Immunology)
Background: There are several mechanisms to describe allergic drug reactions yet the methods to diagnose them are limited.